Peningkatan Aktivitas dan Hasil Belajar Siswa pada Tema 8 Peristiwa Alam melalui Model Kooperatif Tipe STAD di Masa Pandemi Covid-19 - Tsausand Banafsas Taqiya; Tri Sugiyono; Aryo Andri Nugroho (Jurnal Paedagogy, 2021)
This study aims to improve student activities and learning outcomes on the theme of 8 natural events through the STAD type cooperative model in grade 1 SDN Pandean Lamper 02 Semarang in the 2020/2021 school year. This study used a classroom action research method which is carried out in three cycles which include the planning, action implementation, observation, and reflection stages. This research instrument used observation, tests, and interview. The data analysis technique used descriptive analysis. The results of this study indicate that the application of the STAD type cooperative learning model can improve learning activities and learning outcomes for grade 1 students at SDN Pandean Lamper 02 Semarang. This is evidenced by the data on the results of student learning activities in the first cycle is 65.85%, in the second cycle it increases by 5.58% then in the third cycle it increases by 11.16% which initially the second cycle is 71.43% then it becomes 82 ,59%. Learning outcomes using the STAD type cooperative learning model in the first cycle were 54%, the second cycle increased by 71%, and in the third cycle increased up to 89%.